2014
DOI: 10.1016/j.surfcoat.2013.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the physicochemical and mechanical properties of optical copper–cobalt oxide thin films through annealing treatment

Abstract: ÔØ Å ÒÙ× Ö ÔØTailoring the physicochemical and mechanical properties of optical copper cobalt oxide thin films through annealing treatment This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 51 publications
5
25
1
Order By: Relevance
“…The two major peaks of Cu 2p 3/2 and Cu 2p 1/2 are located at 934.2 and 954.0 eV, respectively. The splitting 18,19 energy is 19.8 eV, which agrees well the literature reported value 28 and indicates the formation of Cu 2+ . The satellite peakson the high energy side, arised from the shake-up transition by a ligand metal 3d charge transfer, also confirm the presence of Cu 2+ .…”
Section: Surface Componentssupporting
confidence: 90%
See 1 more Smart Citation
“…The two major peaks of Cu 2p 3/2 and Cu 2p 1/2 are located at 934.2 and 954.0 eV, respectively. The splitting 18,19 energy is 19.8 eV, which agrees well the literature reported value 28 and indicates the formation of Cu 2+ . The satellite peakson the high energy side, arised from the shake-up transition by a ligand metal 3d charge transfer, also confirm the presence of Cu 2+ .…”
Section: Surface Componentssupporting
confidence: 90%
“…The component at binding energy of ~532 eV is assigned to the surface oxygen from a wide variety of species such as chemisorbed or dissociated oxygen or hydroxyl species as well as carbonate groups. [27][28][29] The small shoulder at around 533 eV could be due to subsurface Ospecies. 30 Among the Co-Cu oxides, both CuO and CuCo 2 O 4 exhibit abundant adsorbed and lattice oxygen, while a lot of lattice oxygen and certain amount of subsurface O-are observed in Co 3 O 4 .…”
Section: Surface Componentsmentioning
confidence: 99%
“…The absorptance of 83.4% (prior to the addition of an antireflection layer) was accomplished using 0.25 M copper acetate and 0.25 M cobalt chloride (Cu/Co ratio=1) with dip-speed 120 mm/min (four cycles). Nanoindentation test using the Berkovich indenter showed that the coatings have a high wear resistance [115][116][117].…”
Section: Cumno X Spinels and Cu X Co Y O Z Spinel-likementioning
confidence: 99%
“…Our coatings (before the addition of antireflection layer) exhibited promising absorptance properties as compared to other selective absorber materials synthesized from more complicated sol-gel process routes [25,26]. The light absorption selectivity behavior is due to the combination of factors of the intrinsic properties of coating, the film thickness and reflectivity properties of substrate [24]. However, to maximize the absorptance in UV-Vis range and to protect the coatings from any degradation due to external factors, an antireflection (AR) layer on the top of the absorber layer is, therefore, needed [27,28].…”
Section: Introductionmentioning
confidence: 89%
“…In our previous studies, we prepared copper cobalt oxide (Cu 2 CoO 3 ) thin film coatings deposited on highly reflecting aluminum substrate via a simple, cost-effective and environmentally-friendly sol-gel dip-coating route [21][22][23][24]. Our coatings (before the addition of antireflection layer) exhibited promising absorptance properties as compared to other selective absorber materials synthesized from more complicated sol-gel process routes [25,26].…”
Section: Introductionmentioning
confidence: 99%